Potential Kittlitz's Murrelet Nesting Habitat in North America - Jonathan J Felis; Michelle L Kissling; Robb SA Kaler; Leah A Kenney; Matthew J Lawonn (USGS Science Data Catalog, 2016)
Using nest records and locations to identify landscape-scale parameters (distance to coast, elevation, slope, and land cover) that provide potential nesting habitat, we produced a final map classifying 12% (70,411 km2) of the lands assessed as potential Kittlitz’s Murrelet nesting habitat with dense but distinct patches located in northern Alaska and a more uninterrupted, narrow band extended across coastal mountainous areas in the Pacific Coastal Mountains, Alaska Peninsula Mountains, and Aleutian Islands. The regional variation in habitat-capable parameter values indicate the Kittlitz’s Murrelet may be able to use a variety of habitats for nesting depending on availability. Future nesting habitat studies that employ spatially random sampling designs will allow for more quantitatively robust modeling of nesting habitat and allow predictive extrapolation to areas where nests have not been located, but likely exist.